Inhibition of Vascular Inflammation by Apolipoprotein A-IV - Shearston, Kate; Tan, Joanne T. M.; Cochran, Blake J.; Rye, Kerry-Anne (Frontiers in Cardiovascular Medicine, 2022)
Background: Apolipoprotein (apo) A-IV, the third most abundant apolipoprotein in human high density lipoproteins (HDLs), inhibits intestinal and systemic inflammation. This study asks if apoA-IV also inhibits acute vascular inflammation. Methods: Inflammation was induced in New Zealand White rabbits by placing a non-occlusive silastic collar around the common carotid artery. A single 1 mg/kg intravenous infusion of lipid-free apoA-IV or saline (control) was administered to the animals 24 h before collar insertion. The animals were euthanised 24 h post-collar insertion. Human coronary artery cells (HCAECs) were pre-incubated with reconstituted HDLs containing apoA-IV complexed with phosphatidylcholine, (A-IV)rHDLs, then activated by incubation with tumour necrosis factor (TNF)-. Cell surface vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) in the TNF-alpha-activated HCAECs was quantified by flow cytometry. VCAM-1, ICAM-1 and 3beta-hydroxysteroid-delta24 reductase (DHCR24) mRNA levels were quantified by real time PCR. Results: ApoA-IV treatment significantly decreased collar-induced endothelial expression of VCAM-1, ICAM-1 and neutrophil infiltration into the arterial intima by 67.6±9.9% (p<0.01), 75.4±6.9% (p<0.01) and 74.4±8.5% (p<0.05), respectively. It also increased endothelial expression of DHCR24 by 2.6-fold (p<0.05). Pre-incubation of HCAECs with (A-IV)rHDLs prior to stimulation with TNF-alpha inhibited VCAM-1 and ICAM-1 protein levels by 62.2±12.1% and 33.7±5.7%, respectively. VCAM-1 and ICAM-1 mRNA levels were decreased by 55.8±7.2% and 49.6±7.9%, respectively, while DHCR24 mRNA expression increased by 3-fold. Transfection of HCAECs with DHCR24 siRNA attenuated the anti-inflammatory effects of (A-IV)rHDLs. Pre-incubation of TNF-alpha-activated HCAECs with (A-IV)rHDLs also inhibited nuclear translocation of the p65 subunit of nuclear factor-kappaB (NF-kappaB), and decreased IkappaBalpha-phosphorylation. Conclusion: These results indicate that apoA-IV inhibits vascular inflammation in vitro and in vivo by inhibiting NF-kappaB activation in a DHCR24-dependent manner.